Doping profile optimisation in bulk FinFET channel and source/drain extension regions for low off–state leakage. (5th December 2014) - Zhang, Keke; Liu, Yunfei; Zhu, Huilong; Zhao, Chao; Ye, Tianchun; Yin, Haizhou
Sub–threshold leakage, punch–through leakage and band–to–band tunnelling (BTBT) leakage are the main components of off–state leakage in extremely scaled bulk FinFETs. By using 3–D process and device simulations, this paper studied the effects of channel and source/drain extension doping profile on these three leakage currents in bulk n–FinFETs with triangular shaped fins. Punch–through stop layer (PTSL) and source/drain extension doping profile have been carefully designed to lower the sub–threshold leakage, punch–through leakage and BTBT leakage. With the optimisation of PTSL implant and source/drain anneal conditions, the optimised n–FinFET exhibits superior short channel control, <65 mV/dec sub–threshold slope and <20 mV/V DIBL, and extremely low off–state leakage, <30 pA/um.